Non-noble metal catalyst for fuel cell as well as preparation method and application of non-noble metal catalyst

By using ZIF-8 as a self-template, one-step pyrolysis is used to prepare Co-N-C catalysts, solving the problems of poor service life of precious metals and complex preparation of non-precious metal catalysts in existing fuel cell catalysts, and achieving the preparation of high-performance catalysts and excellent oxygen reduction reaction activity.

CN119864434AActive Publication Date: 2025-04-22HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202510129337.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-04-22
Estimated Expiration
2045-02-05

AI Technical Summary

Technical Problem

A large amount of precious metal platinum is used in existing fuel cell catalysts, which is costly and has poor service life. In addition, non-precious metal catalysts such as Co-N-C have problems of cobalt agglomeration and complex process during the preparation process.

Method used

The metal frame compound ZIF-8 is used as a self-template to prepare a high-performance Co-N-C catalyst by one-step pyrolysis method to avoid agglomeration of cobalt nanoparticles and improve the dispersion and activity of the catalyst.

Benefits of technology

The obtained Co-N-C catalyst exhibits excellent oxygen reduction reaction activity in alkaline and acidic electrolytes, and its stability and anti-methanol toxicity performance are better than traditional Pt/C catalysts, and has good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864434A_ABST
    Figure CN119864434A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of new energy materials and application, and relates to a non-noble metal catalyst for a fuel cell as well as a preparation method and application thereof. The non-noble metal catalyst with the high-activity component Co-N-C is obtained by taking a metal framework compound ZIF-8 as a self-template and adopting a one-step pyrolysis mode, cobalt nano particles in the material are uniformly dispersed in nitrogen-containing porous carbon, and the catalyst has relatively good reaction activity, shows excellent catalytic oxygen reduction performance in a three-electrode system, and can be used for preparing a catalyst for catalytic oxygen reduction. And the material has a good application prospect in fuel cells and other new energy devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a non-precious metal catalyst used in a fuel cell oxygen reduction catalytic reaction and a method for preparing the catalyst, belonging to the field of new energy materials and applications, and relates to a non-precious metal catalyst for a fuel cell and a method for preparing the catalyst and an application thereof. Background Art

[0002] Hydrogen fuel cells that can run and operate at low temperatures (0-200°C) have always been favored as a sustainable energy conversion device for the future. However, due to the large amount of precious metal platinum used in commercial catalysts Pt / C, for example, patent 202410453556.X discloses a platinum-based intermetallic compound catalyst, a preparation method, a membrane electrode, and a fuel cell, and uses an organic matter containing a thiol group as a complexing agent to prepare a highly ordered platinum-based intermetallic compound catalyst. Patent 202410328792.9 discloses a binary Pt-based ordered alloy fuel cell catalyst and a preparation method thereof; the above patent uses platinum to prepare fuel cell catalysts, which is expensive and has an unsatisfactory service life, and its commercialization progress has always been difficult. Therefore, the development of high-quality and low-cost fuel cell catalysts, especially oxygen reduction reaction (ORR) catalysts based on battery cathodes, has always been the direction that people have been pursuing unremittingly.

[0003] Among many non-precious metal oxygen reduction catalysts, although Fe-NC has higher catalytic activity, Co-NC is considered to be the most promising material system because it can catalyze the Fenton reaction to produce free radicals, which then attack the proton membrane, causing thinning of the proton membrane, surface roughness, cracks and pinholes, affecting proton conductivity, gas diffusion and permeation, and proton membrane stability. In Co-NC catalysts, the ORR reaction activity depends on the amount of CoNx, but in the prior art, the catalyst prepared by Co-NC simply increases the cobalt content, causing Co agglomeration, resulting in defects such as poor catalytic performance. At the same time, the preparation process is complicated and the raw materials are expensive. Therefore, it is urgent to provide a high-performance Co-NC catalyst and synthesis method that can be obtained by one-step pyrolysis. Summary of the invention

[0004] The purpose of the present invention is to provide a non-precious metal catalyst for fuel cells, a preparation method and application thereof, using the metal framework compound ZIF-8 as a self-template, and a high-performance Co-NC catalyst is obtained by one-step pyrolysis. The obtained non-precious metal catalyst for fuel cells exhibits excellent catalytic oxygen reduction performance in alkaline and acidic electrolytes, and has good application prospects in fuel cells and other energy devices.

[0005] The technical solution provided by the present invention is as follows:

[0006] A method for preparing a non-precious metal catalyst for a fuel cell comprises the following steps:

[0007] Dissolving zinc salt and cobalt salt in deionized water as a first solution;

[0008] Dissolve 2-methylimidazole and triethylamine in deionized water as a second solution;

[0009] The first solution is added dropwise to the second solution, and the reaction is stirred and then centrifuged to separate the solid matter;

[0010] The solid matter is washed, vacuum dried, ground, and then pyrolyzed to obtain a non-precious metal catalyst (Co-NC catalyst) for fuel cells.

[0011] The above method uses ZIF-8 as a self-template to obtain highly dispersed cobalt nanoparticles, thereby effectively avoiding the agglomeration of cobalt nanoparticles, and a high-performance Co-NC catalyst can be obtained through a one-step pyrolysis.

[0012] Furthermore, the zinc salt is one or more of zinc nitrate, zinc sulfate, and zinc chloride, and the cobalt salt is one or more of cobalt nitrate, cobalt chloride, cobalt oxalate, cobalt sulfate, and cobalt acetate; preferably, the zinc nitrate is zinc nitrate hexahydrate, and the cobalt nitrate is cobalt nitrate hexahydrate; the types of zinc salt and cobalt salt may affect the composition, structure, and performance of the final catalyst. By selecting different zinc salts and cobalt salts, key performance indicators such as the activity, selectivity, and stability of the catalyst can be regulated to meet the needs of fuel cells in different application scenarios.

[0013] Furthermore, the molar ratio of zinc salt to cobalt salt is (1-50): 1. Different zinc-cobalt ratios can make the Co-NC catalyst have different particle sizes, and controlling the ratio of zinc nitrate to cobalt nitrate within a suitable range can make the Co-NC catalyst have a better particle size.

[0014] Furthermore, the molar ratio of 2-methylimidazole to triethylamine is (0.1-1): 1. Controlling 2-methylimidazole and triethylamine within a suitable range can achieve a better carbonization effect of ZIF-8.

[0015] Furthermore, the total molar ratio of the metal ions in the first solution to the 2-methylimidazole in the second solution is 1:(1-10). By controlling the metal ions and 2-methylimidazole within a suitable range, the first solution and the second solution can be controlled within a suitable range, and the catalyst can have better ORR activity.

[0016] Further, the first solution is added dropwise to the second solution and stirred for reaction, wherein the stirring time is 20 to 50 minutes and the rotation speed is 300 to 800 rpm. Controlling the stirring time and rotation speed of the first solution and the second solution can make the first solution and the second solution have a better reaction effect, and make the cobalt atoms and the nitrogen-doped carbon substrate play a better synergistic effect.

[0017] Furthermore, the centrifugal speed is 500-3000 rpm. Controlling the centrifugal speed of the mixture of the first solution and the second solution can better separate the solid product.

[0018] In one embodiment, the pyrolysis temperature is 500-1000°C, and the pyrolysis time is 1-10 h. Controlling the pyrolysis temperature and time of the reaction product of the first solution and the second solution mixture can make the obtained catalyst have better sintering effect and stability, and show ORR activity as good as Pt / C in both alkaline and acidic systems.

[0019] Furthermore, the solid obtained after centrifugation is pyrolyzed at high temperature under an inert atmosphere, wherein the inert atmosphere is a nitrogen or argon atmosphere. The high temperature pyrolysis under an inert gas atmosphere can improve the stability of the product.

[0020] Furthermore, after the first solution is added dropwise to the second solution, the stirring reaction time is 20 to 50 minutes and the rotation speed is 300 to 800 rpm. Appropriate stirring time and rotation speed help to form catalyst particles with uniform structure and narrow particle size distribution. This helps to increase the specific surface area and number of active sites of the catalyst, thereby improving its catalytic performance.

[0021] The present invention also provides a non-precious metal catalyst for a fuel cell, which is prepared by the above method.

[0022] The present invention also provides the use of the above-mentioned non-precious metal catalyst for fuel cells in the preparation of fuel cells resistant to methanol poisoning.

[0023] Beneficial Effects

[0024] The present invention uses deionized water as a solvent, and cobalt-doped ZIF-8 is simply and efficiently synthesized under the action of triethylamine, and a high-performance Co-NC catalyst can be obtained by one-step pyrolysis. This method uses ZIF-8 as a self-template to obtain highly dispersed cobalt nanoparticles, thereby effectively avoiding the agglomeration of cobalt nanoparticles. At the same time, thanks to the synergistic effect of cobalt atoms and nitrogen-doped carbon substrates, the catalyst exhibits ORR activity that is as good as Pt / C in both alkaline and acidic systems. The 10h stability test shows that the Co-NC catalyst decays to 92.9%, which is 16.8% higher than Pt / C. It also has excellent methanol resistance, so it has good application prospects in fuel cells and other energy devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The Zn obtained by using ZIF 8 as the self-template in Examples 1-3 and Comparative Example 1 1-x Co x XRD pattern of (MeIM)2 (x = 0, 0.05, 0.075, 0.1);

[0026] Figure 2 XRD patterns of Co-NCx obtained using ZIF 8 as self-template in Examples 1-3 and Comparative Example 1 (x=0, 0.05, 0.075, 0.1);

[0027] Figure 3 The ORR performance comparison diagram of Co-NCx and Pt / C with different cobalt contents obtained using ZIF 8 as a self-template in alkaline solution in Examples 1-3 and Comparative Example 1 is shown;

[0028] Figure 4 Graph showing the stability and methanol resistance of Co-NC-0.05 with different cobalt contents obtained using ZIF 8 as the self-template in Example 1 in alkaline solution. DETAILED DESCRIPTION

[0029] Example 1

[0030] 1) Dissolve 0.6952 g of zinc nitrate hexahydrate and 0.0358 g of cobalt nitrate heptahydrate in 50 mL of deionized water, referred to as solution A. The molar ratio of zinc nitrate hexahydrate to cobalt nitrate heptahydrate is 95:5.

[0031] 2) Dissolve 1.642 g of 2-methylimidazole and 3 mL of triethylamine in 50 mL of deionized water as solution B. The molar ratio of 2-methylimidazole to triethylamine is 1:1. The molar ratio of the total molar number of metal ions in step 1) to the molar number of 2-methylimidazole in step 2) is 1:8.

[0032] 3) Slowly add solution A to solution B, stir for 30 min at 500 rpm, and centrifuge to obtain a purple solid.

[0033] 4) The solid obtained in step 2) was re-dispersed in deionized water for 24 h, then centrifuged and washed, and vacuum dried at 100° C. for 24 h. The obtained solid was ground into powder with a vacuum degree of -0.08 to -0.1 MPa.

[0034] 5) The powder obtained in step 3) was pyrolyzed at 1000° C. for 3 hours under an inert atmosphere to prepare a Co-NC-0.05 catalyst.

[0035] Example 2

[0036] 1) Dissolve 0.6769 g of zinc nitrate hexahydrate and 0.0537 g of cobalt nitrate heptahydrate in 50 mL of deionized water, referred to as solution A. The molar ratio of zinc nitrate hexahydrate to cobalt nitrate heptahydrate is 92.5:7.5.

[0037] 2) Dissolve 1.642 g of 2-methylimidazole and 3 mL of triethylamine in 50 mL of deionized water as solution B. The molar ratio of 2-methylimidazole to triethylamine is 1:1. The molar ratio of the total molar number of metal ions in step 1) to the molar number of 2-methylimidazole in step 2) is 1:8.

[0038] 3) Slowly add solution A to solution B, stir for 30 min at 500 rpm, and centrifuge to obtain a purple solid.

[0039] 4) The solid obtained in step 2) was re-dispersed in deionized water for 24 h and then centrifuged and washed, and vacuum dried at 100 °C for 24 h. The obtained solid was ground into powder with a vacuum degree of -0.08 to -0.1 MPa.

[0040] 5) The powder obtained in step 3) was pyrolyzed at 1000° C. for 3 hours under an inert atmosphere to prepare a Co-NC-0.075 catalyst.

[0041] Example 3

[0042] 1) Dissolve 0.6586 g of zinc nitrate hexahydrate and 0.07160 g of cobalt nitrate heptahydrate in 50 mL of deionized water, referred to as solution A. The molar ratio of zinc nitrate hexahydrate to cobalt nitrate heptahydrate is 90:10.

[0043] 2) Dissolve 1.642 g of 2-methylimidazole and 3 mL of triethylamine in 50 mL of deionized water as solution B. The molar ratio of 2-methylimidazole to triethylamine is 1:1. The molar ratio of the total molar number of metal ions in step 1) to the molar number of 2-methylimidazole in step 2) is 1:8.

[0044] 3) Slowly add solution A to solution B, stir for 30 min at 500 rpm, and centrifuge to obtain a purple solid.

[0045] 4) The solid obtained in step 2) was re-dispersed in deionized water for 24 h and then centrifuged and washed, and vacuum dried at 100 °C for 24 h. The obtained solid was ground into powder with a vacuum degree of -0.08 to -0.1 MPa.

[0046] 5) The powder obtained in step 3) was pyrolyzed at 1000° C. for 3 hours under an inert atmosphere to prepare a Co-NC-0.1 catalyst.

[0047] Comparative Example 1

[0048] 1) Dissolve 0.732 g of zinc nitrate hexahydrate in 50 mL of deionized water, referred to as solution A.

[0049] 2) Dissolve 1.642 g of 2-methylimidazole and 3 mL of triethylamine in 50 mL of deionized water as solution B. The molar ratio of 2-methylimidazole to triethylamine is 1:1. The molar ratio of the total molar number of metal ions in step 1) to the molar number of 2-methylimidazole in step 2) is 1:8.

[0050] 3) Slowly add solution A to solution B, stir for 30 min at 500 rpm, and centrifuge to obtain an off-white solid.

[0051] 4) The solid obtained in step 2) was re-dispersed in deionized water for 24 h and then centrifuged and washed, and vacuum dried at 100 °C for 24 h. The obtained solid was ground into powder with a vacuum degree of -0.08 to -0.1 MPa.

[0052] 5) The powder obtained in step 3) was pyrolyzed at 1000°C for 3 hours under an inert atmosphere to prepare a Co-NC-0 catalyst.

[0053] The phase structure of the prepared samples can be characterized by X-ray diffraction (XRD). Figure 1 As shown, Zn 1-x Co xAll peaks of the (MeIM)2 precursor are in excellent agreement with those of the simulated ZIF-8, which proves that the precursor has high crystallinity and similar zeolite structure. Through further high-temperature pyrolysis, we directly obtained Co-NC catalysts with different Co doping amounts. Figure 2 It can be seen that the peak at about 22.8° corresponds to the C(002) crystal plane, and the other peak at about 44.3° is attributed to metal β-Co (PDF: 15-0806). At the same time, with the increase of Co doping amount, it can be inferred from the Scherrer equation that the particle size of Co metal particles in the Co-NC catalyst gradually increases, which indicates that high Co content will lead to the sintering of Co in the catalyst. At the same time, in the XRD spectrum, no obvious Co metal particles were found in NC and Co-NC-0.05 after carbonization of ZIF-8. This indicates that the increase of Zn content leads to the spatial isolation of Co and thus inhibits the sintering of Co.

[0054] To evaluate the electrocatalytic performance of Co-NC, we used linear sweep voltammetry in 0.1 M KOH solution to test the performance at different rotation speeds. Figure 3 As shown in the figure, by comparing the half-wave potential (E1 / 2) of the RDE polarization curve, it can be seen that Co-NC-0.05 has the best ORR activity, while the NC without Co doping (carbonized ZIF-8) has the worst performance. More importantly, the half-wave potential of Co-NC-0.05 (0.84V vs RHE) is comparable to that of 20 wt% Pt / C (0.84 V vs RHE), which is higher than the performance of some other reported non-precious metal electrocatalysts. This shows that the Co-NC synthesized in this experiment has a high electrocatalytic ORR activity.

[0055] The stability of the catalyst and its ability to resist methanol poisoning are also important indicators for evaluating the quality of the catalyst. Figure 4 It can be seen that Co-NC-0.05 exhibits better resistance to methanol poisoning and stability. Through the chronoamperometric curve tested at 1600 rpm, it can be found that after 10 h, the performance of Co-NC-0.05 decayed to 92.9%, while Pt / C decayed to 76.1%. In addition, after adding 3 M methanol to the electrolyte, the CV curve of Co-NC-0.05 and the original cathode ORR current remained almost unchanged, while the corresponding current on Pt / C instantly changed from cathode ORR current to reverse anode current. This shows that methanol undergoes an oxidation reaction on Pt / C, and Co-NC-0.050 has excellent resistance to methanol poisoning.

[0056] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0057] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a non-precious metal catalyst for a fuel cell, characterized in that: The steps include: Dissolving zinc salt and cobalt salt in deionized water as a first solution; Dissolve 2-methylimidazole and triethylamine in deionized water as a second solution; The first solution is added dropwise to the second solution, and the reaction is stirred and then centrifuged to separate the solid matter; The solid matter is washed, vacuum dried, ground and then pyrolyzed to obtain a non-precious metal catalyst for fuel cells.

2. The method for preparing a non-precious metal catalyst for a fuel cell according to claim 1, characterized in that: The zinc salt is one or more of zinc nitrate, zinc sulfate and zinc chloride, and the cobalt salt is one or more of cobalt nitrate, cobalt chloride, cobalt oxalate, cobalt sulfate and cobalt acetate.

3. The method for preparing a non-precious metal catalyst for a fuel cell according to claim 1, characterized in that: The molar ratio of zinc salt to cobalt salt is (1-50):

1.

4. The method for preparing a non-precious metal catalyst for a fuel cell according to claim 1, characterized in that: The molar ratio of 2-methylimidazole and triethylamine is (0.1-1):

1.

5. The method for preparing a non-precious metal catalyst for a fuel cell according to claim 1, characterized in that: The molar ratio of the total molar number of metal ions in the first solution to the molar number of 2-methylimidazole in the second solution is 1:(1-10).

6. The method for preparing a non-precious metal catalyst for a fuel cell according to claim 1, characterized in that: The centrifugal rotation speed is 500-3000 rpm.

7. The method for preparing a non-precious metal catalyst for a fuel cell according to claim 1, characterized in that: The pyrolysis temperature is 500-1000° C., and the pyrolysis time is 1-10 h.

8. The method for preparing a non-precious metal catalyst for a fuel cell according to claim 1, characterized in that: After the first solution is added dropwise to the second solution, the stirring reaction time is 20 to 50 minutes at a rotation speed of 300 to 800 rpm.

9. A non-precious metal catalyst for a fuel cell, characterized in that: Prepared by the method according to any one of claims 1 to 8.

10. Use of the non-precious metal catalyst for fuel cells according to claim 9 in the preparation of fuel cells resistant to methanol poisoning.

Citation Information

Patent Citations

  • Binary Pt-based ordered alloy fuel cell catalyst and preparation method thereof

    CN118231683A

  • Platinum-based intermetallic compound catalyst, preparation method, membrane electrode and fuel cell

    CN118336008A

  • Synthesis method of non-noble metal catalyst for fuel cell

    CN112002911A

  • Preparation method and application of non-noble metal catalyst with surface sunken structure

    CN114976046A

  • Preparation method of transition metal composite site carbon-based catalyst, catalyst obtained by preparation method and application of catalyst

    CN115377441A